Cold War America Through the Eyes of a European Writer. W ślady Kolumba (In the Footsteps of Columbus) by Melchior Wańkowicz and Journey Through America by Wolfgang Koeppen - Galant, Jan (Porównania, 2025)
The aim of this article is to conduct a comparative analysis of the travelogues from journeys to America: Wolfgang Koeppen’s Journey Through America and Melchior Wańkowicz’s trilogy W ślady Kolumba (In the Footsteps of Columbus), which both authors wrote in the late 1950s and early 1960s. It is also an attempt at answering the question of whether and how the experience of the Cold War affected the image of America they offer. The article characterizes the different strategies of reporting the trip and shows how the Cold War experience influenced the perception of emigrant communities. For Koeppen, the essence of the emigrant life in America was the necessity of starting over while for Wańkowicz, it was the power of expansion and entrepreneurship.